Past to Future South Atlantic Overturning Circulation: upper-ocean pathways and low-frequency variability - Oliveira, Fernanda Marcello de (2021)
The pathways which compose the upper limb of the Global Overturning Circulation are investigated in the South Atlantic sector. These are comprised by a northward advection of waters starting at the southeastern corner of the basin which brings Pacific and Indian Ocean contributions through the 1) Benguela Current - 2) South Equatorial Current - 3) North Brazil Undercurrent system all the way into the Northern Hemisphere and its subpolar region in order to compensate the process of deepwater formation. The spatio-temporal evolution of the flow is addressed, with focus on the low-frequency variability and response to climate change. Assuming that the South Atlantic subtropical gyre (SASG) and the upper limb of the Atlantic Meridional Overturning Circulation (AMOC) are coupled systems, the interplay between these large-scale oceanic features is explored. This is accomplished through three independent investigations. First, CESM1-POP2 simulation results point to an intensification and southward displacement of the SASG circulation system from the 20th into the 21st century, associated with increased equatorward transport at the western boundary, along the AMOC upper limb. Secondly, subtropical western South Atlantic circulation changes between natural climate extremes of the Last Millennium are addressed with the CESM1-Last Millennium Ensemble Project, revealing a weaker (stronger) anticyclonic SASG circulation during the warm (cold) period, with decreased (increased) northward transport associated with the AMOC upper limb. Lastly, the forced response of South Atlantic pathways which are linked to the AMOC and the SASG are illustrated in historical simulations and future projections, according to a pessimistic radiative forcing scenario (the RCP8.5), by the 40-member ensemble mean of the CESM1-Large Ensemble. Up- to downstream long-term trends are found, linked to an observed and projected AMOC weakening as well as to wind-forced upper ocean circulation changes, according to the recent scientific literature. Considering the primary research findings of these three investigations, this thesis provides important contributions to the understanding of the time-evolving dynamics of fundamental circulation systems in view of unprecedented human-induced climate change.